Many Ingredients, One Sublime Dish: The Recipe for the Passage of Illinois HB5412 Into Law. Issue 3 (July 2015) - Baté-Ambrus, Venoncia M.; Castillo, Amparo; Martinez, Erica; Campbell, Jamie; Boughton-Price, Leticia; Gutierrez Kapheim, Melissa; Arrom, José O.; Hernandez, Wandy; Waddy, Jeffery; Castillo, Sheila; Schaps, Margie; Williams, Yolonda
Abstract : This article contextualizes the need for Illinois House Bill 5412 (HB5412), which calls for the establishment of a state board to create recommendations for the community health worker (CHW) field in Illinois, including a scope of practice, core competencies, training and certification standards, and sustainable funding and reimbursement mechanisms. Multisectorial partnerships and their outputs, coupled with frontline CHW interventions, created a synergistic climate conducive to the passing of this historic CHW legislation. This article provides a timeline and recipe for legislative success as described through processes and activities collaboratively undertaken, concentrating on a 5-year period (2009-2014).